A grain boundary diffusion method suitable for sintered rare earth permanent magnet materials with high cerium content
By using an aluminum-containing diffusion source and a two-stage aging treatment in high-cerium-content sintered rare-earth permanent magnet materials, the grain boundary wettability and diffusion efficiency of heavy rare-earth elements were improved, the problem of insufficient intrinsic coercivity enhancement in high-Ce materials was solved, and production costs were reduced.
Patent Information
- Application Number
- CN202611313873.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-11-03
AI Technical Summary
Existing technologies cannot effectively solve the problems of insufficient grain boundary wettability, low diffusion efficiency, and insufficient grain boundary phase continuity of heavy rare earth elements in high-cerium content sintered rare earth permanent magnet materials, which limits the improvement of intrinsic coercivity and increases production costs.
By combining an aluminum-containing diffusion source with the surface of a high-cerium substrate, and by synergistically adjusting the Al content and the temperature and time of the secondary aging treatment, the wettability and diffusion efficiency of heavy rare earth elements at the grain boundaries are improved, thereby promoting the effective diffusion and enrichment of heavy rare earth elements in the high-cerium substrate.
It improves the intrinsic coercivity of high-cerium sintered rare earth permanent magnet materials, reduces the cost of rare earth raw materials, and increases the utilization rate of the diffusion layer. It is highly adaptable and suitable for the production of high Ce content materials.
Smart Images

Figure CN123033889A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of rare earth permanent magnet materials and their grain boundary control technology, specifically to a grain boundary diffusion method applicable to high cerium content sintered rare earth permanent magnet materials. Background Technology
[0002] Sintered rare-earth permanent magnet materials are widely used in new energy vehicles, wind power generation, industrial motors, and electronic devices due to their high remanence, coercivity, and energy product. To further improve the intrinsic coercivity of sintered rare-earth permanent magnet materials, existing technologies typically employ grain boundary diffusion. This involves placing a diffuser containing heavy rare-earth elements such as Tb and Dy on the magnet surface and then subjecting it to high-temperature diffusion and subsequent aging treatment. This allows the heavy rare-earth elements to diffuse inward along the magnet's grain boundaries, forming a heavy rare-earth-rich region at the outer edge of the main phase grains. This improves the magnet's coercivity with a relatively small increase in the amount of heavy rare-earth elements used.
[0003] To reduce the raw material cost of sintered rare earth permanent magnet materials, Ce can be used to partially replace Nd or Pr in existing technologies. However, as the Ce content in the magnet increases, especially when Ce accounts for more than 11% of the total mass of the magnet, the composition of the grain boundary phase, the liquid phase formation temperature, the wetting behavior, and the phase transformation process after diffusion all change significantly. This makes it difficult to directly apply the grain boundary diffusion source and subsequent heat treatment regime, which were originally suitable for sintered rare earth permanent magnet materials with low Ce content, to materials with high Ce content.
[0004] For sintered rare earth permanent magnet materials with high Ce content, when using conventional heavy rare earth diffusion sources for grain boundary diffusion, problems such as insufficient wetting of the magnet surface and Ce-rich grain boundary phase by the diffusion source, decreased effective transport capacity of heavy rare earth elements along the grain boundary, and insufficient continuity of the grain boundary phase after diffusion are likely to occur. As a result, the number of heavy rare earth elements that enter the interior of the magnet and actually play a role is limited, the utilization rate of the diffusion layer is low, and the improvement of intrinsic coercivity of high Ce substrate after grain boundary diffusion is limited.
[0005] Furthermore, existing grain boundary diffusion processes typically optimize the diffusion source composition and subsequent aging conditions separately, lacking a synergistic control method for the grain boundary characteristics of high-Ce-content sintered rare-earth permanent magnet materials. Simply increasing the amount of heavy rare-earth elements not only increases production costs but also fails to fundamentally improve the grain boundary wetting and diffusion efficiency of high-Ce materials. Therefore, it is necessary to provide a grain boundary diffusion scheme suitable for high-Ce-content sintered rare-earth permanent magnet materials. By synergistically adjusting the diffusion source composition and subsequent aging conditions, the grain boundary diffusion efficiency and utilization rate of heavy rare-earth elements in high-Ce substrates can be improved, thereby obtaining higher intrinsic coercivity. Summary of the Invention
[0006] To address the aforementioned problems, this invention provides a grain boundary diffusion method suitable for sintered rare earth permanent magnet materials with high cerium content, which can effectively overcome the shortcomings of the prior art.
[0007] This invention is achieved through the following technical solution: a grain boundary diffusion method suitable for high-cerium-content sintered rare-earth permanent magnet materials, comprising: The step of providing a high-cerium substrate involves providing a high-cerium substrate, wherein the high-cerium substrate is a sintered rare-earth permanent magnet material, and the mass fraction of Ce in the high-cerium substrate is greater than 11% of the total mass of the high-cerium substrate. The aluminum-containing diffusion source preparation steps include preparing an aluminum-containing diffusion source, wherein the aluminum-containing diffusion source comprises heavy rare earth elements and Al; The diffusion source setting step involves placing the aluminum-containing diffusion source on the surface of the high-cerium substrate. The grain boundary diffusion step involves performing grain boundary diffusion treatment on a high-cerium substrate in which the aluminum-containing diffusion source is provided, so that the heavy rare earth elements in the aluminum-containing diffusion source diffuse along the grain boundaries of the high-cerium substrate into the interior of the high-cerium substrate. The aging process involves sequentially performing a first-stage aging treatment and a second-stage aging treatment on the high-cerium substrate after grain boundary diffusion treatment. Specifically, by synergistically adjusting the Al content in the aluminum-containing diffusion source and the temperature and holding time of the secondary aging treatment, the wetting of the grain boundary phase of the high-cerium substrate by the aluminum-containing diffusion source and the transport of heavy rare earth elements along the grain boundary are improved, and the redistribution of the grain boundary phase and the heavy rare earth enrichment region after diffusion is promoted, thereby obtaining a high-cerium sintered rare earth permanent magnet diffused through grain boundaries.
[0008] As a preferred technical solution, the mass fraction of Ce in the high-cerium substrate is 11%-15%, and the intrinsic coercivity Hcj of the high-cerium substrate at room temperature before grain boundary diffusion treatment is 14.0-16.0 kOe.
[0009] As a preferred technical solution, the aluminum-containing diffusion source comprises 60%-95% heavy rare earth elements, 5%-20% Al and 0%-20% auxiliary alloying elements by mass percentage, and the sum of the mass percentages of each component is 100%.
[0010] As a preferred technical solution, the heavy rare earth element includes at least one of Tb and Dy, the auxiliary alloying element includes at least one of Cu, Ga and Fe, and Al accounts for 5%-10% of the total mass of the aluminum-containing diffusion source.
[0011] As a preferred technical solution, the temperature of the first-stage aging treatment is 850-950℃, and the holding time is 20-30h; the temperature of the second-stage aging treatment is 600-700℃, and the holding time is 3-5h.
[0012] As a preferred technical solution, the aluminum-containing diffusion source is any one of alloy powder, slurry, thin strip, coating or preform; when the aluminum-containing diffusion source is a slurry, the aluminum-containing diffusion source powder is mixed with a volatile carrier and a binder to form a slurry, and then applied to the surface of the high-cerium substrate by at least one of spraying, brushing, screen printing or dip coating; the grain boundary diffusion treatment and the first-stage aging treatment are carried out continuously in the same batch or separately.
[0013] The present invention discloses an aluminum-containing diffusion source for grain boundary diffusion in high-cerium-content sintered rare-earth permanent magnet materials. By mass percentage, the source comprises 60%-95% heavy rare-earth elements, 5%-20% Al, and 0%-20% auxiliary alloying elements. The heavy rare-earth elements include at least one of Tb and Dy, and the auxiliary alloying elements include at least one of Cu, Ga, and Fe. The sum of the mass percentages of all components is 100%. The aluminum-containing diffusion source is disposed on the surface of a high-cerium sintered rare-earth permanent magnet substrate with a Ce mass fraction greater than 11%, and provides heavy rare-earth elements and Al to the high-cerium sintered rare-earth permanent magnet substrate during grain boundary diffusion.
[0014] As a preferred technical solution, Al accounts for 5%-10% of the total mass of the aluminum-containing diffusion source, and the aluminum-containing diffusion source is any one of alloy powder, slurry, thin strip, coating or preform; when the aluminum-containing diffusion source is alloy powder, the average particle size D50 of the alloy powder is 3-8μm, and the maximum particle size is not greater than 25μm.
[0015] The present invention discloses a high-cerium sintered rare-earth permanent magnet, which is prepared by a grain boundary diffusion method. In the high-cerium sintered rare-earth permanent magnet, Ce accounts for more than 11% of the total mass of the high-cerium sintered rare-earth permanent magnet, and the high-cerium sintered rare-earth permanent magnet has an intrinsic coercivity Hcj increment of 8.0-10.0 kOe compared with the high-cerium substrate before grain boundary diffusion treatment.
[0016] As a preferred technical solution, the mass fraction of Ce in the high-cerium sintered rare earth permanent magnet is 11%-15%, and the intrinsic coercivity Hcj of the high-cerium substrate before grain boundary diffusion treatment is 14.0-16.0 kOe at room temperature. After the grain boundary diffusion treatment, first-stage aging treatment and second-stage aging treatment, the high-cerium sintered rare earth permanent magnet forms a grain boundary region enriched with heavy rare earth elements.
[0017] The beneficial effects of the present invention are as follows: 1. The present invention uses an aluminum-containing diffusion source containing heavy rare earth elements and Al. The Al improves the wetting state between the diffusion source and the surface of the high Ce substrate and the grain boundary phase, which is conducive to the formation of a more continuous grain boundary diffusion channel, thereby promoting the effective diffusion of heavy rare earth elements such as Tb and Dy into the interior of the magnet along the grain boundary, and improving the diffusion efficiency and utilization rate of heavy rare earth elements.
[0018] 2. This invention coordinates the Al content in the aluminum-containing diffusion source with the temperature and holding time of the secondary aging treatment. While suppressing excessive coarsening of the main phase grains and excessive tempering, it promotes the redistribution and continuity of Ce-rich grain boundary phases, Al-rich grain boundary phases, and heavy rare earth enrichment regions, thereby improving the grain boundary structure of the diffused magnet and enhancing the intrinsic coercivity of high Ce sintered rare earth permanent magnet materials.
[0019] 3. This invention mainly optimizes high Ce sintered rare earth permanent magnet materials with a Ce mass fraction greater than 11%. Without relying solely on increasing the amount of heavy rare earth elements, it can significantly improve the problem of insufficient diffusion gain in high Ce material systems by conventional grain boundary diffusion methods. It reduces the cost of using rare earth raw materials such as Nd and Pr while taking into account the magnetic properties of the magnet.
[0020] 4. The aluminum-containing diffusion source of the present invention can be set on the surface of a high-cerium substrate in various forms such as alloy powder, slurry, thin strip, coating or preform, and can be combined with existing grain boundary diffusion and heat treatment processes. It has strong process adaptability and is easy to implement in the production process of high-Ce sintered rare earth permanent magnet materials. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 This is a flowchart of the grain boundary diffusion method for high-cerium-content sintered rare-earth permanent magnet materials according to the present invention. Detailed Implementation
[0023] All features disclosed in this specification, or all steps in all disclosed methods or processes, may be combined in any way, except for mutually exclusive features and / or steps.
[0024] Any feature disclosed in this specification (including any appended claims, abstract, and drawings) may be replaced by other equivalent or similar features for a similar purpose, unless specifically stated otherwise. That is, unless specifically stated otherwise, each feature is merely one example of a series of equivalent or similar features.
[0025] like Figure 1As shown, this embodiment provides a grain boundary diffusion method suitable for sintered rare earth permanent magnet materials with high cerium content. This method mainly targets grain boundary control in sintered rare earth permanent magnet materials with high Ce content, so as to improve the problems of insufficient grain boundary wettability, low transport efficiency of heavy rare earth elements, and insufficient continuity of grain boundary phase after diffusion in high Ce materials by conventional heavy rare earth grain boundary diffusion methods.
[0026] Unless otherwise stated, all percentages in this specification are by weight. High-cerium substrate refers to a substrate in which Ce accounts for more than 11% of the total mass of the sintered rare-earth permanent magnet; low-cerium substrate refers to a control substrate in which Ce accounts for less than 4% of the total mass of the magnet.
[0027] High-cerium substrates can be prepared using conventional powder metallurgy methods, including alloy melting or rapid solidification, hydrogen crushing, air jet milling, magnetic field orientation pressing, cold isostatic pressing, vacuum sintering, and pretreatment. The overall composition of the candidate substrate may include one or more of Nd, Pr, Dy, Ce, Fe, B, Cu, Ga, Al, Co, and Zr, with Ce preferentially replacing a portion of Nd and / or Pr.
[0028] Innate resistance H cj Measurements were taken at room temperature using a hysteresis loop test apparatus, and the unit is kOe. H cj The increment equals the diffusion and the completion of two stages of time. H cj Subtract the same batch of substrates before diffusion H cj To ensure the comparison is effective, all embodiments and comparative examples should use the same dimensions, orientation, surface condition, and test temperature.
[0029] Example 1 The high-cerium substrate shown in Table 1 was used, with a Ce content of 12.50%. The initial sample after processing and surface treatment... H cj It is 15.0 kOe.
[0030] The Al-containing diffusion source D-Al from Table 2 was used, which consists of 80.0% Tb, 10.0% Al, and 10.0% Cu. The diffusion source was applied to two 10 mm × 10 mm surfaces of the sample and then dried.
[0031] After drying, the samples underwent a first-stage aging treatment at 900℃ for 25 h, followed by cooling and a second-stage aging treatment at 650℃ for 4 h, before cooling to room temperature. It was predicted that the obtained high-cerium sintered rare-earth permanent magnets... H cj It is 23.5 kOe, relative to the substrate before diffusion.H cj The increment is 8.5 kOe; considering fluctuations in raw materials and processes, H cj The reasonable prediction range for the increment is 8.2-8.8 kOe.
[0032] The results indicate that for a high-cerium substrate with a Ce content of 12.5%, a diffusion source containing 10.0% Al combined with a two-stage aging process of 650 °C–4 h is expected to improve the wetting of the Ce-rich grain boundary phase by the diffusion source and the effective transport of heavy rare earth elements along the grain boundaries, and promote the continuity of the grain boundary phase after diffusion.
[0033] Comparative Example 1 The high-cerium substrate shown in Table 1 was used, with a Ce content of 12.5%. The initial sample after processing and surface treatment... H cj It is 15.0 kOe.
[0034] The Al-containing diffusion source D-0 from Table 2 was used, which consists of 90.0% Tb and 10.0% Cu. The diffusion source was applied to two 10 mm × 10 mm surfaces of the sample and then dried.
[0035] After drying, the samples underwent a first-stage aging treatment at 900℃ for 25 h, followed by cooling and a second-stage aging treatment at 650℃ for 4 h, before cooling to room temperature. It was predicted that the obtained high-cerium sintered rare-earth permanent magnets... H cj It is 20.0 kOe, relative to the substrate before diffusion. H cj The increment is 5.0 kOe; considering fluctuations in raw materials and processes, H cj The reasonable prediction range for the increment is 4.7-5.3 kOe.
[0036] This result indicates that for a high-cerium substrate with a Ce content of 12.5%, under the same process with an Al-free diffusion source, H cj The significant decrease in the increment indicates that Al diffusion in high Ce magnets has a gain effect.
[0037] Comparative Example 2 The low-cerium substrate in Table 1 was used, with a Ce content of 3.0%. The initial sample after processing and surface treatment... H cj It is 15.0 kOe.
[0038] The Al-containing diffusion source D-Al from Table 2 was used, which consists of 80.0% Tb, 10.0% Al, and 10.0% Cu. The diffusion source was applied to two 10 mm × 10 mm surfaces of the sample and then dried.
[0039] After drying, the samples underwent a first-stage aging treatment at 900℃ for 25 h, followed by cooling and a second-stage aging treatment at 650℃ for 4 h, before cooling to room temperature. It was predicted that the obtained low-cerium sintered rare-earth permanent magnets... H cj It is 24.0 kOe, relative to the substrate before diffusion. H cj The increment is 9.0 kOe; considering fluctuations in raw materials and processes, H cj The reasonable prediction range for the increment is 8.7-9.3 kOe.
[0040] This group is used to evaluate the effectiveness of high-Ce substrate optimization schemes when directly applied to low-Ce substrates.
[0041] Comparative Example 3 The low-cerium substrate in Table 1 was used, with a Ce content of 3.0%. The initial sample after processing and surface treatment... H cj It is 15.0 kOe.
[0042] The Al-containing diffusion source D-0 from Table 2 was used, which consists of 90.0% Tb and 10.0% Cu. The diffusion source was applied to two 10 mm × 10 mm surfaces of the sample and then dried.
[0043] After drying, the samples underwent a first-stage aging treatment at 900℃ for 25 h, followed by cooling and a second-stage aging treatment at 650℃ for 4 h, before cooling to room temperature. It was predicted that the obtained low-cerium sintered rare-earth permanent magnets... H cj It is 24.0 kOe, relative to the substrate before diffusion. H cj The increment is 9.5 kOe; considering fluctuations in raw materials and processes, H cj The reasonable prediction range for the increment is 9.2-9.8 kOe.
[0044] Comparative Example 2 and Comparative Example 3 H cj The increments were all in the range of approximately 9 kOe, and neither the Al diffusion source nor the optimized secondary aging regime showed a positive gain on low Ce substrates. Given that the above data are predicted values and have not yet been statistically tested, it is inappropriate to conclude from this that there is a significant difference between the two groups.
[0045] substrate Table 1 Substrate Composition Rapidly solidified flakes of various alloys were hydrogen-crushed and air-jet milled to produce magnetic powder with an average particle size D50 of 3.0-3.8 μm. This powder was then pressed in an orientation magnetic field of at least 1 T and subjected to cold isostatic pressing at approximately 200 MPa. The pressed compacts were vacuum sintered at 1040-1080 °C for 3-5 h, and after pretreatment, processed into 10 mm × 10 mm × 3 mm sheet samples, with the magnetization orientation along the 3 mm thickness. By fine-tuning the sintering and pretreatment processes, the room-temperature intrinsic coercivity of the two substrates before grain boundary diffusion was optimized. H cj Both are approximately 15.0 kOe.
[0046] The two 10 mm × 10 mm surfaces of the sample were sequentially ground or polished, degreased, and ultrasonically cleaned with anhydrous ethanol, with the surface roughness Ra controlled to be no greater than 0.8 μm. Each embodiment or comparative example used samples with similar dimensions, orientation, and initial magnetic properties from the same substrate batch.
[0047] Al-containing diffusion source D-Al and conventional diffusion source D-0 were set up, and their candidate compositions are shown in Table 2. Both diffusion sources were melted under argon protection and then rapidly solidified, crushed and sieved to obtain alloy powders with D50 of 3-8 μm and a maximum particle size of no more than 25 μm.
[0048] diffusion source Table 2 Diffusion Source Components The diffusion source powder was mixed with terpineol and other substances to form a coatable slurry, which was then uniformly coated on two 10 mm × 10 mm surfaces of the sample and dried at 80 °C for 30 min.
[0049] Magnetic properties Innate resistance H cj Measurements were taken at 25±2℃ using a hysteresis loop tester, and the unit is kOe. H cj The increment equals the diffusion and the completion of two stages of time. H cj Subtract the same sample before diffusion H cj .
[0050] Table 3 Magnetic Properties Alternative implementation methods Without departing from the concept of the present invention, the heavy rare earth elements may be Tb, Dy, or a combination of both; the aluminum-containing diffusion source may be applied by powder coating, vapor deposition, sputtering, patching, or paste; grain boundary diffusion and primary aging may be carried out continuously in the same furnace or in separate furnaces.
[0051] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions conceived without inventive effort should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope defined in the claims.
Claims
1. A grain boundary diffusion method suitable for sintered rare earth permanent magnet materials with high cerium content, characterized in that, include: The step of providing a high-cerium substrate involves providing a high-cerium substrate, wherein the high-cerium substrate is a sintered rare-earth permanent magnet material, and the mass fraction of Ce in the high-cerium substrate is greater than 11% of the total mass of the high-cerium substrate. The aluminum-containing diffusion source preparation steps include preparing an aluminum-containing diffusion source, wherein the aluminum-containing diffusion source comprises heavy rare earth elements and Al; The diffusion source setting step involves placing the aluminum-containing diffusion source on the surface of the high-cerium substrate. The grain boundary diffusion step involves performing grain boundary diffusion treatment on a high-cerium substrate in which the aluminum-containing diffusion source is provided, so that the heavy rare earth elements in the aluminum-containing diffusion source diffuse along the grain boundaries of the high-cerium substrate into the interior of the high-cerium substrate. The aging process involves sequentially performing a first-stage aging treatment and a second-stage aging treatment on the high-cerium substrate after grain boundary diffusion treatment. Specifically, by synergistically adjusting the Al content in the aluminum-containing diffusion source and the temperature and holding time of the secondary aging treatment, the wetting of the grain boundary phase of the high-cerium substrate by the aluminum-containing diffusion source and the transport of heavy rare earth elements along the grain boundary are improved, and the redistribution of the grain boundary phase and the heavy rare earth enrichment region after diffusion is promoted, thereby obtaining a high-cerium sintered rare earth permanent magnet diffused through grain boundaries.
2. The grain boundary diffusion method for high-cerium-content sintered rare-earth permanent magnet materials according to claim 1, characterized in that, The high-cerium substrate has a Ce mass fraction of 11%-15%, and the room temperature intrinsic coercivity Hcj of the high-cerium substrate before grain boundary diffusion treatment is 14.0-16.0 kOe.
3. The grain boundary diffusion method for high-cerium-content sintered rare-earth permanent magnet materials according to claim 1, characterized in that, The aluminum-containing diffusion source comprises 60%-95% heavy rare earth elements, 5%-20% Al, and 0%-20% auxiliary alloying elements by mass percentage, with the sum of the mass percentages of each component being 100%.
4. The grain boundary diffusion method for high-cerium-content sintered rare-earth permanent magnet materials according to claim 3, characterized in that, The heavy rare earth element includes at least one of Tb and Dy, the auxiliary alloying element includes at least one of Cu, Ga and Fe, and Al accounts for 5%-10% of the total mass of the aluminum-containing diffusion source.
5. The grain boundary diffusion method for high-cerium-content sintered rare-earth permanent magnet materials according to claim 1, characterized in that, The first-stage aging treatment is carried out at a temperature of 850-950℃ for 20-30 hours; the second-stage aging treatment is carried out at a temperature of 600-700℃ for 3-5 hours.
6. The grain boundary diffusion method for high-cerium-content sintered rare-earth permanent magnet materials according to claim 1, characterized in that, The aluminum-containing diffusion source is any one of alloy powder, slurry, thin strip, coating or preform; when the aluminum-containing diffusion source is a slurry, the aluminum-containing diffusion source powder is mixed with a volatile carrier and a binder to form a slurry, and then applied to the surface of the high-cerium substrate by at least one of spraying, brushing, screen printing or dip coating; the grain boundary diffusion treatment and the first-stage aging treatment are carried out continuously in the same batch or separately.
7. An aluminum-containing diffusion source for grain boundary diffusion in high-cerium-content sintered rare-earth permanent magnet materials, characterized in that, The substrate comprises, by mass percentage, 60%-95% heavy rare earth elements, 5%-20% Al, and 0%-20% auxiliary alloying elements. The heavy rare earth elements include at least one of Tb and Dy, and the auxiliary alloying elements include at least one of Cu, Ga, and Fe. The sum of the mass percentages of each component is 100%. The aluminum-containing diffusion source is used to be disposed on the surface of the high-cerium sintered rare earth permanent magnet substrate with a Ce mass fraction greater than 11%, and provides heavy rare earth elements and Al to the high-cerium sintered rare earth permanent magnet substrate during grain boundary diffusion.
8. The aluminum-containing diffusion source for grain boundary diffusion in high-cerium-content sintered rare-earth permanent magnet materials according to claim 7, characterized in that, The Al accounts for 5%-10% of the total mass of the aluminum-containing diffusion source, and the aluminum-containing diffusion source is any one of alloy powder, slurry, thin strip, coating or preform; when the aluminum-containing diffusion source is alloy powder, the average particle size D50 of the alloy powder is 3-8μm, and the maximum particle size is not greater than 25μm.
9. A high-cerium sintered rare-earth permanent magnet, characterized in that, The high-cerium sintered rare-earth permanent magnet is prepared by the grain boundary diffusion method according to any one of claims 1-6, wherein the mass fraction of Ce in the high-cerium sintered rare-earth permanent magnet is greater than 11% of the total mass of the high-cerium sintered rare-earth permanent magnet, and the high-cerium sintered rare-earth permanent magnet has an intrinsic coercivity Hcj increment of 8.0-10.0 kOe relative to the high-cerium substrate before grain boundary diffusion treatment.
10. The high-cerium sintered rare-earth permanent magnet according to claim 9, characterized in that, The high-cerium sintered rare-earth permanent magnet has a Ce mass fraction of 11%-15%, and the room temperature intrinsic coercivity Hcj of the high-cerium substrate before grain boundary diffusion treatment is 14.0-16.0 kOe. After the grain boundary diffusion treatment, first-stage aging treatment and second-stage aging treatment, the high-cerium sintered rare-earth permanent magnet forms a grain boundary region enriched with heavy rare earth elements.
